PENGARUH MEDIA VIDEO ANIMASI CERITA RAKYAT DIGITAL TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 101764 BANDAR KLIPPA - Josep Nainggolan; Zainuddin Muchtar; Eva Betty Simanjuntak; Masta Marselina Sembiring; Irsan Rangkuti (STKIP Subang, 2026)
Currently, students' reading comprehension skills are still relatively low. This study aims to determine the effect of digital folklore animated video media on the reading comprehension skills of class IV students at SD Negeri 101764 Bandar Klippa. This type of research was quantitative research. The research method used was a quasi-experimental design with a nonequivalent control group design using a pretest and posttest. The population used consisted of class IV students at SD Negeri 101764 Bandar Klippa, totaling 69 students. The sample was selected using purposive sampling technique, consisting of 24 students in class IV-A and 25 students in class IV-C. Data collection techniques used were tests, observation, and documentation. The research instrument in the form of a multiple-choice test was tested for validity and reliability prior to use. The data were analyzed using the normality test (Shapiro-Wilk), homogeneity test (Levene), hypothesis testing (independent sample t-test), and N-gain test. The posttest average score of the experimental class was higher (78.29) compared to the control class average (67.99). Based on the data obtained from the hypothesis test, the t_count > t_table value was 2.418 > 2.011, thus H₀ was rejected and H_a was accepted. Then also the n-gain value in the control class was obtained at 27.22% with a low category with an interpretation of less effective, while in the experimental class the n-gain value was obtained at 56.02% in the medium category with an interpretation of quite effective. It can be concluded that there is a significant influence of the use of digital folklore animation video media on the reading comprehension ability of fourth grade students of SDN 101764 Bandar Klippa.